ANALISIS MANAJEMEN MODAL KERJA PADA PT. JASA RAHARJA (PERSERO) - Gabriella Anggriany Kaunang; Jhony Revo Tampi; Jan Wonok (JURNAL ADMINISTRASI BISNIS, 2014)
Working capital is one part of the existing assets within the company or cooperative that is in use by the company in day-to-day activities, in this case is to determine the extent to which the level of achievement that has earned company. Puspose of this paper is to determine how to analyze financial statements using, sources and uses of working capital, and working capital adequacy ratio. In the assessment of working capital calculations performed using analysis of sources and uses of working capital and capital adequacy ratio by the formula: Working capital to total assets ratio, current leabilities to net working capital, working capital turnover, which shows that the company is increasing every year. The results of the above analysis it can be seen that the working capital management on PT. Jasa Raharja (Persero) has been very effective because of the insurance business saw revenue each year there is an increase to it so that it remains effective and the company maintained its liquidity level course companies must be able to observe and manage well so that this increase will continue in the years to come. Keywords : Working Capital, Technical Analysis, Financial Statements.